Changes in the Stress-Strain State of Precast Reinforced Concrete Floor Systems in Masonry Multi-Storey Buildings after Non-Design Impacts - Hasenko, Anton; Kudlai, Andrii (Academic journal Industrial Machine Building Civil Engineering, 2025)
The article is devoted to investigating non-design impacts on precast reinforced concrete floor systems of multistorey brick buildings that arise during military actions. The study examines the influence of both external and internal factors on these structural systems and their deterioration. Using the materials of the “Report on the Detailed Survey of the Residential Building in Chernihiv, damaged as a Result of Military Actions”, prepared by the State Research Institute of Building Structures (NDIBK) in 2022, the paper analyses the nature of the effects of military actions on the building as a whole and on its individual structural components, with particular attention to precast reinforced concrete floor systems. The case considered involves multiple direct artillery strikes on the building, which resulted in partial destruction of load-bearing structures and damage (or failure) of the associated floor elements. The findings of the analysis of this specific case provide a basis for further search, investigation, and development of new, more effective methods for restoring the serviceability of damaged precast reinforced concrete floor systems. This task remains highly relevant today and must consider not only the efficiency of restoration but also the safety of personnel working or residents living in buildings undergoing repair.
Keywords: residential buildings; impact of military actions; damage; restoration; reinforced concrete floor; serviceability